Exercise or lie down? The impact of fitness app use on users' wellbeing - Cai, Jie; Li, Gang (Frontiers in Public Health, 2024)
Introduction The use of fitness apps is becoming more and more widespread, and its impact on people's well-being has received more and more attention. Methods The relationship between fitness app use and users' well-being and the influence mechanism was explored using structural equation modeling with upward social comparison as the mediating variable and self-control as the moderating variable. Results The questionnaire survey of 1,452 fitness app users over 18 years old shows that: (1) fitness app use is associated with users' well-being; (2) upward social comparison plays a mediating role in the relationship between fitness app use and users' well-being; (3) self-control has a moderating effect on the relationship between fitness app use and users' well-being. Discussion Self-control plays a significant moderating role between social comparison and well-being, upward social comparison can improve the well-being of high self-control users but reduce the well-being of low self-control users.